Normal serum alanine aminotransferase and non-alcoholic fatty liver disease among Korean adolescents: a cross-sectional study using data from KNHANES 2010-2015 - Yunkoo Kang; Sowon Park; Seung Kim; Hong Koh (BMC, 2018)
Abstract Background Non-alcoholic fatty liver disease (NAFLD) is complicated disease and increasing worldwide. Previously, many studies of NALFD prevalences have used alanine aminotransferase (ALT) of > 40 U/L to define NAFLD, although that is too high to be reliable among adolescents. This study aimed to define the upper normal limit of ALT among Korean adolescents, and use it to estimate the prevalence of NAFLD, based on data from the Korea National Health and Nutrition Examination Survey (KNHANES). Methods Data were obtained from 1785 healthy adolescents (916 boys and 869 girls, 10-18 years old) who participated in the KNHANES during 2010-2015. The International Diabetes Federation metabolic syndrome criteria for adolescents were used to exclude participants with metabolic syndrome components. Furthermore, participants who previously had diseases related to low HDL levels, high TG levels, diabetes, or very low/high body mass index and hepatitis B were excluded. The 95th percentiles level of ALT from healthy participants were evaluated. The definition of NAFLD was overweight status (≥85th percentile of body mass index) plus elevated ALT levels (95th percentile). Results The upper normal ALT were 24.1 U/L for boys and 17.7 U/L for girls. Based on these values, the estimated prevalences of NAFLD in 2015 were 8.9% among adolescents. Conclusion Defining the upper normal limit of ALT can be adjusted for each sex and ethnics in the general population. ALT laboratory thresholds used for children should be re-examined. The physicians should be aware not to underdiagnose NAFLD patient even ALT level is < 40 U/L.